2014
DOI: 10.1080/02692171.2013.872086
|View full text |Cite
|
Sign up to set email alerts
|

Domestic demand and global production in the Eurozone: A multi-regional input-output assessment of the global crisis

Abstract: This paper studies the effects of domestic and foreign demand impulses in euro area economies following the Great Recession of 2008-09 and the Eurozone crisis of 2011-12. Using a global input-output framework we apply a set of metrics to assess spillover and feedback effects triggered by the dynamics of final demand. Our findings suggest that cross-country trade spillovers have had a moderate impact as compared to the role of domestic sources of final demand in explaining the contraction in income and employme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…They show that the more a sector is globally central in the country network, the largest its impact. Similar results are stressed by the recent and growing literature on trade in value added and its implication on the transmission of shocks via international trade (e.g., see Garbellini & Wirkierman, ; Johnson & Noguera, ; Nagengast & Stehrer, and Tukker & Dietzenbacher, , among others). Building on this literature and on Gabaix (), Di Giovanni and Levchenko () and Eaton, Kortum, and Sotelo () show that international trade amplifies the "granularity" of an economy and hence its sensitivity to sectoral shocks.…”
Section: Propagation Of Shocks and Key Sectors In Input‐output Networsupporting
confidence: 81%
“…They show that the more a sector is globally central in the country network, the largest its impact. Similar results are stressed by the recent and growing literature on trade in value added and its implication on the transmission of shocks via international trade (e.g., see Garbellini & Wirkierman, ; Johnson & Noguera, ; Nagengast & Stehrer, and Tukker & Dietzenbacher, , among others). Building on this literature and on Gabaix (), Di Giovanni and Levchenko () and Eaton, Kortum, and Sotelo () show that international trade amplifies the "granularity" of an economy and hence its sensitivity to sectoral shocks.…”
Section: Propagation Of Shocks and Key Sectors In Input‐output Networsupporting
confidence: 81%
“… These numbers are reported in Foster, Stehrer, and Timmer (), Garbellini, Marelli, and Wirkierman (), and Ederer and Reschenhofer (). Note also that the share of imported intermediates in global manufacturing output is only 16%; the share of imported intermediates in global production of goods and services is 8% (Baldwin & Lopez‐Gonzalez, ).…”
mentioning
confidence: 67%
“…12 In other words, less than a fifth of the GDP in Southern Europe depends on foreign sources of demand. The lesson that we draw from these numbers is 12 These numbers are reported in Foster, Stehrer, and Timmer (2013), Garbellini, Marelli, and Wirkierman (2014), and Ederer and Reschenhofer (2016). Note also that the share of imported intermediates in global manufacturing output is only 16%; the share of imported intermediates in global production of goods and services is 8% (Baldwin & Lopez-Gonzalez, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…61 This is the conclusion of a recent investigation (Garbellini, Marelli and Wirkierman, 2014) that has quantified, within an input-output framework, the possible benefits deriving for the eurozone countries from such a coordinated policy. In the same paper, it has been found that during the Great Recession the "Piigs" have generally been more sensitive to domestic demand reductions while core-eurozone countries have been more vulnerable to (and inflicting more damage to) their trade partners.…”
Section: Reforms In the Governance Of The Emumentioning
confidence: 99%